A Kinematic Study of Progressive Micrographia in Parkinson's Disease - Zham, Poonam; Raghav, Sanjay; Kempster, Peter; Poosapadi Arjunan, Sridhar; Wong, Kit; Nagao, Kanae J.; Kumar, Dinesh K. (Frontiers in Neurology, 2019)
Progressive micrographia is decrement in character size during writing and is commonly associated with Parkinson’s disease (PD). This study has investigated the kinematic features of progressive micrographia during a repetitive writing task. Twenty-four PD patients with duration since diagnosis of less than 10 years and 24 age-matched controls wrote the letter ‘e’ repeatedly. PD patients were studied in defined off states, with scoring of motor function on the Unified Parkinson’s Disease Rating Scale Part III. A digital tablet captured x-y coordinates and ink-pen pressure. Customized software recorded the data and offline analysis derived the kinematic features of pen-tip movement. The average size of the first and the last five letters were compared, with progressive micrographia defined as greater than 10% decrement in letter stroke length. The relationships between dimensional and kinematic features for the control subjects and for PD patients with and without progressive micrographia were studied. Differences between the initial and last letter repetitions within each group were assessed by Wilcoxon signed-rank test, and the Kruskal-Wallis test was applied to compare the three groups. There are five main conclusions from our findings: (i) 66% of PD patients who participated in this study exhibited progressive micrographia; (ii) handwriting kinematic features for all PD patients was significantly lower than controls (p<0.05); (iii) patients with progressive micrographia lose the normal augmentation of writing speed and acceleration in the x axis with left-to-right writing and show decrement of pen-tip pressure (p=0.034); (iv) kinematic and pen-tip pressure profiles suggest that progressive micrographia in PD reflects poorly sustained net force: (v) although progressive micrographia resembles the sequence effect of general bradykinesia, we did not find a significant correlation with overall motor disability, nor with the aggregate UPDRS-III bradykinesia scores for the dominant arm.